Undergraduate Specialist Program in Pathobiology at the University of Toronto - Douglas M. Templeton PhD, MD; Avrum I. Gotlieb MD, CM, FRCPC (Elsevier, 2017)
Following a merger of the Departments of Pathology, Clinical Biochemistry, and part of Medical Microbiology, our faculty agreed to deliver a new, unique undergraduate program "Specialist in Pathobiology" at the University of Toronto, in order to teach current concepts of mechanisms of disease to students selected from the large undergraduate science population. The emphasis was on molecular and cellular aspects of pathogenesis and not on the clinical practice of laboratory medicine and pathology. Based on the then new Department of Laboratory Medicine and Pathobiology, we drew upon our large faculty and new recruits in both basic and clinical science to deliver a new curriculum that is unique and dynamic. We began admitting students in 2000, and we have now graduated our 15th class. In this study, we describe our philosophy and goals for the program, and report its success based on student outcomes and innovative course offerings.